The Importance of Paediatrics in Developing Countries - Thomas Stapleton (Paediatrica Indonesiana, 1975)
The rate of tuberculous infection is high. In many areas by the age of ten to fourteen years almost half the population have become tuberculin positive, not as a result of BCG vaccination, but as a result of infection acquired from someone in their environment.The fact that you have selected paediatric emergencies as one of the themes of this congress is merely a reflection that the overall mortality of children admitted to the children’s wards in a great teaching hospital such as you have here in Surabaya is of the order of fifteen to twenty per cent.